VIETNAMESE NON-ENGLISH MAJOR EFL UNIVERSITY STUDENTS’ RECEPTIVE KNOWLEDGE OF THE MOST FREQUENT ENGLISH WORDS - Ngoc Yen, Dang Thi (VNU Journal of Foreign Studies; Vol 36 No 3DO - 10.25073/2525-2445/vnufs.4553, 2020)
The receptive knowledge of 442 non-English major university students in a General English program in Vietnam was measured with Webb, Sasao, and Ballance’s (2017) New Vocabulary Levels Test. It was found that despite 10 years of formal English language instruction, nearly half of the participants had not mastered the most frequent 1,000 words and more than 90% had not mastered the most frequent 2,000 words. The study calls for more attention to high-frequency words in English language instruction in Vietnamese EFL context.